Mechanistic insights into chloride‐related heart failure progression according to the plasma volume status - Hajime Kataoka (ESC Heart Failure)
Abstract Aims Two types of heart failure (HF) progression were recently proposed on the basis of an increased vs. non‐increased serum chloride concentration. The applicability of this concept to real‐world HF pathophysiology requires further investigation. The present study evaluated the mechanisms of HF progression to a different type according to changes in the estimated plasma volume status (ePVS). Methods and results Data from 47 patients (32% men; 78.2 ± 9.7 years of age) with stable to worsening HF (37.5 ± 16 days) were analysed. Physical examination, standard blood tests, and b‐type natriuretic peptide (BNP) measurements were conducted. The ePVS was calculated as follows: ePVS (dL/g) = [100 − haematocrit (%)]/[haemoglobin (g/dL)]. For the study subjects as a whole (n = 47), changes in the ePVS correlated positively with changes in the serum chloride concentration from stable to worsening HF (r = 0.398, P = 0.0056). When divided into two groups of worsening HF with an increased (n = 31) vs. non‐increased serum chloride concentration (n = 16), no significant baseline differences in body weight, serum logBNP, or ePVS were detected between groups. Under worsening HF, the increase in body weight (2.34 ± 1.12 vs. 2.59 ± 1.56 kg, P = 0.57) and logBNP (0.39 ± 0.30 vs. 0.54 ± 0.31 pg/mL, P = 0.13) did not differ between groups, but the increase in the ePVS was smaller in the group with a non‐increased serum chloride concentration compared with that with an increased serum chloride concentration (0.292 ± 0.49 vs. 0.653 ± 0.60 dL/g, P = 0.044). An increase in the %change in ePVS ≥ 10% was less common in patients with a non‐increased chloride concentration (37% vs. 71%, P = 0.03). Patients with a non‐increased serum chloride concentration had more HF signs (3.31 ± 0.79 vs. 2.65 ± 0.71, P = 0.005) and a higher incidence of pulmonary rales (63% vs. 16%, P = 0.0024) than those with an increased serum chloride concentration. Conclusions According to the changes in the ePVS, HF progression may result from a difference between two HF types (i.e. increased vs. non‐increased serum chloride concentration) in the cardiac reserve in response to a given cardiac burden by modulating plasma volume status via the possible tonicity potential of chloride.